Farm typology for targeting fertilizer advisory – digital green and fertilizer Ethiopia use cases - Pawar, R.R.; Ismael, A.D.; Descheemaeker, K.; Liben, F.; Ebrahim, M.; Eshete, M.; Tigabie, A.; Tsedalu, B.; Desta, G.; Tamene, Lulseged D.; Aubert, C.; Assefa, B.; et al. (International Institute of Tropical Agriculture, 2024)
The EiA Initiative is organized around Use Cases located in the Global South, including Cambodia, Colombia, Democratic Republic of the Congo, Egypt, Ethiopia, Ghana, Ivory Coast, Kenya, Malawi, Mali, Mexico, Morocco, Nigeria, Peru, the Philippines, Rwanda, Senegal, Uganda, Vietnam, Zambia and Zimbabwe (CGIAR, 2023). The lessons learned on each Use Case will provide evidence to develop lessons at global application. Each Use Case has been working on the co-creation of Minimum Viable Products (MVP) that provides agronomic advice at scale. In order to maximize the impact potential of the MVP by each Use Case, a household survey has been performed at country scale, initially in Ethiopia to gain insights into relevant areas such as gender dynamics and farmer diversity that may affect adoption potential of the MVP. The collected data is the base to construct and analyse the different farm typologies across different geographies and commodities. To do the Farm Typology analysis of the Ethiopian Use Cases, EiA approached Plant Production Systems, group of Wageningen University (WUR), with the request to clean, process and analyse the collected data, elaborate a Farm Typology and socialize the methodology of this report in a format of protocol to be use by Use Case leaders. This report involves three steps: 1) data analysis framework; 2) construction of the farm typology; and 3) presentation of a protocol to understand and execute the R scripts developed during the data analysis. This document represents all three steps in a systematic manner. It starts with an introduction indicating the aims of the farmer segmentation and the used data framework (chapter 1), followed with the methods we used for the typology construction (chapter 2) and the outcomes of the analysis as results and discussion (chapter 3 and 4).